Findings in Chinese Patients With Parkinson's Disease: A Content Analysis From the SML Study - Qian, Yiwei; Zhang, Yi; He, Xiaoqin; Xu, Shaoqing; Yang, Xiaodong; Mo, Chengjun; Lu, Xiaomeng; Qiu, Mengjuan; Xiao, Qin (Frontiers in Psychiatry, 2021)
Social media listening is a new process for obtaining information from social media platforms to generate insights into users’ experiences and has been used to analyze discussions about a multitude of diseases. To understand Parkinson’s disease patients’ unmet needs and optimize communication between doctors and patients, social media listening was performed to investigate concerns in Chinese patients. A comprehensive search of publicly available social media platforms with Chinese-language content posted between January 2005 and April 2019 in mainland China was performed using defined Parkinson’s disease-related terms. After multiple steps of machine screening were performed, a series of posts were derived. The content was summarized and classified manually to analyze and map psychological insights, and descriptive statistics were applied to aggregate findings. A total of 101,899 patient-related posts formed the basis of this study. The topics mainly focused on motor symptoms (n=54,983), choice of pharmaceutical drugs (n=45,203) and nonmotor symptoms (n=44,855). The most common symptoms mentioned were tremor (54.5%), pain (22.9%) and rigidity (22.1%). Psychological burden (51%) and work/social burden (48%) were the most concerning burdens for patients and their families. The compound levodopa (43%) and dopamine agonists (23%) were the most common options for the patients, while concerns about new-generation anti-Parkinson’s disease medication increased. The portraits of patients suggested varying characteristics across different periods and advocate for personalized service from doctors. In the management of patients, it is imperative to plan individualized therapy and education strategies as well as strategies for social support.